Objects Monitoring RADAR using Bluetooth Ultrasonic - Karjadi, Daniel Avian; Haryono , Haryono (Politeknik Ganesha Medan, 2022)
Currently the development of information technology is very fast in its development. Up to all fields can not be separated from information technology. In the industrial era 4.0, there are also a lot of Internet of Things devices. Almost every field has used many IoT devices. The presence of IoT-based devices is very helpful in modern human life today. Moreover, with the development of microcontrollers and open source makes someone create a device quickly. One of them is making a prototype for sensing objects. By utilizing the Arduino Uno microcontroller and Ultrasonic sensors to create a sensing prototype. The results of this sensing can be displayed on notebooks and mobile phones. The microcontroller also sends sensing sensor data via Bluetooth as a wireless communication medium. Called Internet of Thing if a device can send signals to other devices. Various data communications can be via wireless or wire. Mobile app that is used to display sensing results from Ultrasonic sensors. Use of the App Inventor platform as a front end for mobile apps. This device is only limited to a short distance. Due to the limitations of the Ultrasonic sensing sensor it does not exceed 1 meter. This prototype can be developed using a longer distance and can be applied to remote sensing, if changing the sensing sensor with a remote sensing sensor.